Geographical variation in community‐wide herbivory matches patterns of intraspecific variation instead of species turnover - Xiang Liu; Ziyuan Lin; Kui Hu; Xingxing Wang; Peng Zhang; Yao Xiao; Li Zhang; Mu Liu (Global Ecology and Biogeography, 2023)
Aim Attempts over the past 30 years to explain geographical variation in the strength of herbivore pressure have given rise to ecological hypotheses like the latitudinal herbivory hypothesis. This hypothesis, however, has rarely been tested using community‐level data. Therefore, the aim of our study was to examine the patterns and potential mechanisms underlying geographical variation in community‐wide herbivory. Location The Qinghai‐Tibetan Plateau. Time Period July 2021. Major Taxa Studied Plants. Methods We selected 43 grassland sites along a 1500‐km latitudinal gradient ( c . 27°N to 39°N) and a 2698‐m elevational gradient (1886–4584 m) on the Qinghai‐Tibetan Plateau. We evaluated geographical patterns in invertebrate herbivory pressure at the population and community levels, while also evaluating the importance of geographical variation in mediating the effects of abiotic and biotic factors on intraspecific variation (through changes in herbivory on component species) and species turnover effects (through changes in plant community composition). Results Community‐wide herbivory decreased with latitude, mirroring intraspecific variation, while species turnover effects did not vary along any tested geographical gradients. Furthermore, we found that geographical variation in community‐wide herbivory was strongly positively correlated with soil nitrogen content. We also found a positive effect of soil nitrogen content on intraspecific variation and a negative effect of plant community biomass on species turnover effects. Main Conclusions The latitudinal gradient in community‐wide herbivory was primarily mediated by intraspecific variation, which was in turn associated with a gradient in soil nitrogen content. Our findings highlight the need for community‐wide assessments of geographical variation in plant–herbivore interactions, decomposing community‐wide herbivory into intraspecific variation and species turnover effects.